Collected papers on Greek colonization - Graham, A. J. (Mnemosyne, Supplements, 2001)
For the first time together in one volume all the papers on Greek colonization published by A. J. Graham over the last forty years. Some of these appeared in publications difficult of access. They will all now be widely available, and thus complement the author's Colony and Mother City in Ancient Greece and his two chapters on the subject in Cambridge Ancient History III.3, second edition. In addition the volume contains one new paper, not previously published, entitled 'Thasian Controversies' . The published papers are reproduced unchanged, except for the correction of misprints, and the original page-numbering is indicated. All the original figures and illustrations are included. There is a comprehensive, analytical, index.